2000
DOI: 10.1007/s002030000197
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the synthesis of H 2 -forming methylenetetrahydromethanopterin dehydrogenase (Hmd) and of HmdII and HmdIII in Methanothermobacter marburgensis

Abstract: Recently it was found that the specific activity of H2-forming methylenetetrahydromethanopterin dehydrogenase (Hmd) in Methanothermobacter marburgensis (formerly Methanobacterium thermoautotrophicum strain Marburg) increased six-fold when the hydrogenotrophic archaeon was grown in chemostat culture under nickel-limited conditions. We report here that the increase is due, at least in part, to increased expression of the hmd gene. This was demonstrated by Northern and Western blot analysis. These techniques were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 28 publications
3
67
0
Order By: Relevance
“…barkeri was clearly affected by Ni level. These results are in line with the fact that the Wood-Ljungdahl pathway for reduction of CO to CH 4 is influenced by Ni depletion in cytochrome-free methanogens, through up-regulation of Ni-free [Fe]-hydrogenase [35]. Consumption of CO in M .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…barkeri was clearly affected by Ni level. These results are in line with the fact that the Wood-Ljungdahl pathway for reduction of CO to CH 4 is influenced by Ni depletion in cytochrome-free methanogens, through up-regulation of Ni-free [Fe]-hydrogenase [35]. Consumption of CO in M .…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, some methanogens without cytochromes have been shown to synthesise a Ni-free [Fe]-hydrogenase, instead of the F 420 -reducing [NiFe]-hydrogenase, under Ni-limiting conditions, thus reducing their need for Ni. This Ni-free [Fe]-hydrogenase is involved in the reduction of CO 2 to CH 4 through reaction 1 [35], and its presence in M . bourgensis MAB1 and M .…”
Section: Discussionmentioning
confidence: 99%
“…Under Ni limiting conditions, the specific activity of this enzyme declines at least 100-fold and it is functionally replaced by two other enzymes that do not require Ni and use a tetrahydromethanopterin cofactor. These two enzymes (an [Fe] hydrogenase and an F 420 -dependent methylenetetrahydromethanopterin dehydrogenase) are up-regulated several fold in response to Ni deficiency (Afting et al, 2000, Thauer et al, 2010). The [Fe] hydrogenase can functionally replace the [NiFe] enzyme for H 2 oxidation, but it is catalytically inferior with a K m for H 2 of 0.2 mM vs. 0.01 mM for the [NiFe] enzyme.…”
Section: Microbial Adaptation and Acclimation To Metal Ion Limitmentioning
confidence: 99%
“…There is no evidence for a hmd gene, hmd isoenzyme genes, or the recently described hmd co-occurring genes in strain DH1 [2]. Gene expression studies in other methanogens have shown that the expression of hmd and the isoenzymes may be regulated by hydrogen and/or also by nickel concentrations, for example, upregulation of hmd under low nickel concentrations [37, 48], but genetic studies have also revealed that hmd may not be required for growth on H 2 and CO 2 [49]. Depending on the environmental conditions some methanogens live in, these findings could help explain the presence and absence of hmd and co-occurring genes in genomes of some hydrogenotrophic methanogens.…”
Section: Resultsmentioning
confidence: 99%